Hubungan Tinggi Badan Ibu Dan Asupan Zat Gizi Makro Dengan Stunting Pada Balita Usia 6-23 Bulan Di Pekon Sumberagung Kecamatan Ambarawa - Arina Sofiyanti; Abdullah Abdullah; Alftulesi Nurhayati; Dera Elva Junita (Journal on Education, 2024)
Stunting in toddlers is caused by two factors, namely direct causes, one of which can be seen from macronutrient intake, and indirect causes can be seen from genetic factors, short maternal height caused by pathological conditions or having genes that carry short traits. The purpose of this study was to determine the relationship between maternal height and macronutrient intake with stunting of toddlers aged 6-23 months in Pekon Sumber Agung, Ambarawa District. Type of quantitative research with cross-sectional design. The study population was toddlers aged 6-23 months in Pekon Sumber Agung Ambarawa District, with a total of 222 and a sample of 119 using the Cluster Sampling technique. This research was conducted in Pekon Sumber Agung Ambarawa District from June 3 to 10, 2024. Data collection methods with anthropometric measurements in the form of height using a microtome and body weight longboard, interviews through 2x 24-hour food recall form sheets. Bivariate analysis in this study used the T-test. This study found that there was no relationship between maternal height and stunting with a P-value of 0.071, there was no relationship between fat intake and stunting P-value of 0.065, and there was a relationship between energy intake and stunting P-value of 0.001 protein P-value 0.006 carbohydrates P-value 0.002. Suggestions for further researchers are expected to add variables or data related to the father's height due to the risk of genetic factors obtained from both parents, namely mothers and fathers and biased consumption surveys using SQ-FFQ to determine the diversity of foods that toddlers have consumed in the past.